Determination of nitrate and nitrite levels of van herby cheese - Abdurrahman Aksoy; Emrullah Sağun; idris Türel; Neşe Okut (Eurasian Journal of Veterinary Sciences)
This study was made to find out the levels of nitrate and nitrite in herby cheese obtained in Van region. 57 samples of herby cheese were used. In all samples of cheese examined were found nitrate and nitrite. In the samples the levels of nitrate and nitrite were found as 32,72-96.96 ppm ( average 60.23 ppm) and 5.52-47.83 ppm { average 20.04 ppm). The high levels of nitrate and nitrite in herby cheese could come from the herbs which are added. As a result, it has been found that the rates of nitrate and nitrite in the examined herby cheese are on a level that could be harmful for health.